Where to direct research in lean six sigma?: Bibliometric analysis, scientific gaps and trends on literature - da Silva, Fabio Francisco [UNESP]; Filser, Lukas Daniel; Juliani, Fernando [UNESP]; de Oliveira, Otávio José [UNESP] (Emerald, 2018)
Purpose: Lean Six Sigma (LSS) is a continuous improvement methodology used to increase the efficiency and effectiveness of processes. Although there are several articles published, only two have analyzed the literature from a bibliometrics perspective. The purpose of this paper is to analyze the LSS literature by bibliometrics, identifying its state of the art, scientific gaps and research trends. Design/methodology/approach: Articles published up to 2016 in the database Scopus were investigated to identify the most significant articles, authors, journals, institutions and countries based on citation counting as well as the most frequent keywords and subject areas on LSS. Articles published in 2014, 2015 and 2016 were analyzed to point out scientific gaps and to identify eight main research trends on LSS. Findings: The research trends are: “LSS implementation”, “Healthcare”, “LSS tools”, “Human factors”, “Expansion of results”, “SME”, “LSS combined with other methodologies” and “Education”. The research outcomes also point out the most significant articles, authors, journals, institutions and countries in LSS literature. Practical implications: This research contributes to develop the state of the art of LSS and helps professionals as well as researchers to identify which issues new studies should address. Originality/value: The performance of the literature is measured based on the number of citations and not on the number of published papers, and the bibliometric analysis covers the highest number of articles so far (319 articles). Besides, the identification of the main research trends on LSS is exclusively based on the most recent studies.
Keywords: Bibliometrics; Lean six sigma; Research trends; Scientific gaps